BEHAVIORS AND ATTITUDES IN THE TEACHING AND LEARNING OF GEOMETRY - Helena Sousa Melo; Maria do Carmo Martins (European Scientific Journal, ESJ, 2015)
This paper presents a case study about teaching and learning topics of Geometry that are part of the syllabus of high school courses. Internationally the teaching of Geometry has been the subject of several studies. Nevertheless, research continues to reveal that Geometry is still quite absent from the classrooms, especially in the early years; Geometry is disliked by most students, is misunderstood, and its notation is totally ignored. One of the reasons for this failure is that these issues are addressed superficially in the curriculum of the training teachers of Geometry. This paper describes the experience of teaching Geometry to a class with 90 students in academic year 2014-2015, enumerates some difficulties and behaviors faced by students and teachers, and exposes the results of the academic success.